Działalność parków krajobrazowych a rozwój regionalny na przykładzie Parku Krajobrazowego Wysoczyzny Elbląskiej - Kruk, Henryk (Landscape Parks Activity and Regional Development on the Example of the Landscape Park of Elbląg's Heights, 2008)
Landscape parks are one of the nature protection forms existing in Poland. These areas are created because of natural, historical, and cultural values existing in the region. The activity of the landscape park contains not only the nature protection, but also other forms. When it is proper, it can also influence economic development of the region. The author presents on the example of the Landscape Parks of the Elbląg's Heights. The article also includes opinions and expectations of the local authorities activities of the park. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 229-238